Evaluation of the impact of chemical control on the ecology of Rattus norvegicus of an urban community in Salvador, Brazil - Pertile, Arsinoê Cristina (2022)
Fundação Oswaldo Fundação Cruz. Secretaria de Vigilância Sanitária do Ministério da Saúde. Wellcome Trust. Fundação de Amparo à Pesquisa do Estado de Bahia (FAPESB).